2014
DOI: 10.1007/s00408-014-9622-5
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Lung T Lymphocytes in a Porcine Model

Abstract: These results suggest that in healthy animals the lung lobes behave as a homogeneous immune organ. T cells were detected in very low percentages at birth and in adult life, which may explain the high susceptibility to respiratory infections both early and later in life. Postweaning antigenic challenges and endocrine and sexual maturity at 3M had important effects on the development of the mucosal immune system. It was also evident that changes at mucosal sites were poorly correlated with PBMC and LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…On the other hand, mucosal immunity is of paramount importance to prevent and control infectious diseases ( 67 ). We compared parenteral (SC) and mucosal (IN) immunization to induce systemic and mucosal immune response and, seeking to avoid tolerance induction and the uncertainty of the mucosal doses administered, a SC/IN protocol was also tested ( 27 , 28 , 45 ). Our results indicated that both IN and SC immunizations stimulate the production of IgA and IgG antibodies, with specific response dynamics and locations ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, mucosal immunity is of paramount importance to prevent and control infectious diseases ( 67 ). We compared parenteral (SC) and mucosal (IN) immunization to induce systemic and mucosal immune response and, seeking to avoid tolerance induction and the uncertainty of the mucosal doses administered, a SC/IN protocol was also tested ( 27 , 28 , 45 ). Our results indicated that both IN and SC immunizations stimulate the production of IgA and IgG antibodies, with specific response dynamics and locations ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…To test the recombinant protein as an intranasal (IN) immunogen, doses containing 200 μg of the antigen in sterile phosphate buffer without adjuvant were prepared following a previously reported protocol ( 45 ). Briefly, doses containing 200 μg of the antigen in sterile phosphate buffer without adjuvant were prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals immunized with recombinant baculoviruses received 5 x 10 8 PFU in the first two doses and 1 x 10 9 PFU in the third and fourth doses, irrespective of the inoculation route. At the end of the experiments, animals were humanely euthanized; bronchoalveolar lavages (BAL) were obtained as detailed in ( 70 ) from pigs immunized with the NG19m antigen.…”
Section: Methodsmentioning
confidence: 99%